Manajemen Pembiayaan Pendidikan di Sekolah Dasar Islam Terpadu Al Fatih Depok - Nurkaidah; Andriyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The operational structure and funding of education is an important component in educational administration management which has the capacity to have a significant impact on the quality of human resources. This study intends to ensure the following: (1) Plan the budget in order to improve educational standards; (2) allocate human resources for the purposes of managing education financing; (3) implementing education financing management; and (4) supervising the education financing system in order to improve standards at SDIT AL FATIH Depok. Qualitative, analytical and descriptive methods were used in this study. Documentation, interviews and observation are the techniques used to obtain data. Data collection, data reduction, data presentation, and drawing conclusions are the four components of Miles and Huberman's interactive analysis model used in the data analysis approach. Credibility, transferability, dependability and confirmability are used in the process of determining data validity.The findings show the following: 1) SDIT AL FATIH Depok prepares and describes education budget planning in the form of RAPBPT, which is implemented at the end of each year by identifying all appropriate programs and budgets. 1) The process of allocating funds for education starts from the source, where the head of the foundation decides on the choices that have been reached through meetings involving stakeholders from the school community and repeats the assessment. Putting human resources in charge of overseeing the money is secondary. The principal is responsible for the financial management of SDIT AL FATIH Depok, in accordance with the organizational structure; The foundation and education department oversee the management of SDIT AL FATIH Depok's education funds. 3. The budget implementation process is used to fund school programs, as well as spending on goods and services, development, and so on. 4. After that, the School Committee, the AL FATIH Depok Foundation, and the Education Office received the school's financial accountability report.